1998
DOI: 10.1159/000026149
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total Cholesterol, Apolipoprotein E {FC12}e4 Allele, and Alzheimer’s Disease

Abstract: The σ4 allele of the apolipoprotein E (apoE) is associated with Alzheimer’s disease (AD) and also with elevated serum total cholesterol and low-density lipoprotein levels. However, the interrelationships between apoE genotype, plasma cholesterol levels and AD risk have been studied very little. We examined the possible role of serum total cholesterol in the pathogenesis of AD in a population-based sample of 444 men, aged 70–89 years, who were survivors of the Finnish cohorts of the Seven Countries Study. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
455
4
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(487 citation statements)
references
References 31 publications
18
455
4
10
Order By: Relevance
“…Experimental studies suggest that cholesterol may promote the accumulation of the amyloid-β peptide (Aβ) and amyloid plaques, a cardinal feature of AD (Refolo et al, 2000;Sparks et al, 1994), and that cholesterol-lowering therapies may reduce the accumulation of Aβ and amyloid plaques (Fassbender et al, 2001;Howland et al, 1998;Hutter-Paier et al, 2004;Refolo et al, 2001;Sparks, 1996). Several longitudinal studies (Kalmijn et al, 2000;Kivipelto et al, 2002;Notkola et al, 1998;Whitmer et al, 2005), but not all (Tan et al, 2003), and one neuropathological study (Pappolla et al, 2003) have reported an association between higher mid-life serum cholesterol levels and a higher risk of subsequent AD. However, epidemiological studies investigating the relationship between late-life serum cholesterol levels and subsequent AD risk have generated conflicting findings (Kivipelto and Solomon, 2006;Mielke et al, 2005), suggesting that our proposed PET endophenotype might have particular value in the assessment of putative mid-life risk factors for AD, reducing the possibility of potentially confounding effects of older age or pre-clinical AD on the putative risk factor and reducing the time and number of subjects needed in a longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies suggest that cholesterol may promote the accumulation of the amyloid-β peptide (Aβ) and amyloid plaques, a cardinal feature of AD (Refolo et al, 2000;Sparks et al, 1994), and that cholesterol-lowering therapies may reduce the accumulation of Aβ and amyloid plaques (Fassbender et al, 2001;Howland et al, 1998;Hutter-Paier et al, 2004;Refolo et al, 2001;Sparks, 1996). Several longitudinal studies (Kalmijn et al, 2000;Kivipelto et al, 2002;Notkola et al, 1998;Whitmer et al, 2005), but not all (Tan et al, 2003), and one neuropathological study (Pappolla et al, 2003) have reported an association between higher mid-life serum cholesterol levels and a higher risk of subsequent AD. However, epidemiological studies investigating the relationship between late-life serum cholesterol levels and subsequent AD risk have generated conflicting findings (Kivipelto and Solomon, 2006;Mielke et al, 2005), suggesting that our proposed PET endophenotype might have particular value in the assessment of putative mid-life risk factors for AD, reducing the possibility of potentially confounding effects of older age or pre-clinical AD on the putative risk factor and reducing the time and number of subjects needed in a longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…An increased risk of Alzheimer's disease has been linked with a natural genetic variant of apolipoprotein E (apoE), a molecule associated with cholesterol metabolism. The ⑀4 allele of apoE, the allele associated with increased risk for late onset AD, has been associated with elevated total serum cholesterol (87,88). Demented patients homozygotic for apoE-4 had the highest total plasma cholesterol levels among a referral population of 40 patients with clinically diagnosed Alzheimer's disease compared with a sample of non-demented elderly controls (89).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in plasma cholesterol level in HFD-induced amnesia corroborated with other study results that elevated serum cholesterol level could be an important risk factor for AD. [4][5][6] Atorvastatin and simvastatin in 5 mg/kg b.w. dose significantly decreased the plasma cholesterol level whereas piracetam did not show any significant change in plasma cholesterol level.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] It appears that cholesterol turnover plays an important role in the deposition and clearance of amyloid peptide in brain. [3][4][5][6] Oxygen free radicals produced within the neurons National Journal of Physiology, Pharmacy and Pharmacology 1294 2017 | Vol 7 | Issue 12 can cause tissue damage and are also implicated in aging and neurodegenerative process. [7,8] The most widely used treatments for AD at present are the reversible acetylcholinesterase inhibitors, which aim at prolonging cognitive functions through decreased degradation of acetylcholine at synaptic cleft.…”
Section: Introductionmentioning
confidence: 99%